ANALISIS DESKRIPTIF KARAKTERISTIK GURU SMK KOTA TERNATE BERBASIS TEORI GLICKMAN SEBAGAI DASAR PENGEMBANGAN SUPERVISI KOLABORATIF - Purwati, Endang; Maisyaroh, Maisyaroh; Sobri, Ahmad Yusuf; Juharyanto, Juharyanto; Sinon, Iriwi Louisa S. (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2026)
This study aims to describe the characteristics of vocational high school (SMK) teachers in Ternate City based on their level of commitment and level of abstraction, to determine appropriate supervisory approaches. Although instructional supervision has been widely examined, studies that map teacher characteristics as a basis for determining supervisory approaches—particularly in the context of vocational education in eastern Indonesia, such as Ternate—remain limited. This research employs a descriptive quantitative approach with a sample of 93 vocational high school teachers selected through random sampling. The instrument was adapted from Glickman’s (1981) theoretical framework and has undergone construct validity and reliability testing (Cronbach’s Alpha α = 0.83 and α = 0.80). Data were analyzed using descriptive statistics. The findings identify four categories of teacher characteristics: teacher dropouts (24%), unfocused workers (28%), analytical observers (21%), and professional teachers (27%). These results indicate that more than half of the teachers have not yet reached the professional category, thus requiring supportive and participatory supervisory approaches. Accordingly, a collaborative supervision approach based on Glickman’s syntax—comprising pre-conference, observation, analysis, post-conference, and post-critique—is recommended as a relevant supervisory strategy. Practically, these findings may serve as a reference for supervisors and school principals in designing differentiated supervision programs aligned with teacher profiles. Theoretically, this study contributes to the literature on mapping teacher characteristics within the context of vocational education in Indonesia.